Cistanche extracts ameliorates the neurotoxicity induced by hydrogen peroxide in new mutant DJ‐1‐transfected neuroblastoma cellular models. Issue 7 (19th June 2019) - An, Chunna; Pu, Xiaoping; Wang, Qi; Zhang, Hongning
Abstract: Introduction: DJ‐1 mutation is a causative reason for familial Parkinson's disease (PD). Leucine166Proline (L166P) and C106S are two important DJ‐1 mutations. In this study, we established hydrogen peroxide (H2 O2 ) induced L166P and C106S DJ‐1‐transfected neuroblastoma (SH‐SY5Y) cellular models of PD and investigated the effects of Cistanche extracts and key bioactive compounds, including acteoside, echinacoside, caffeic acid, and Cistanche total glycosides on these two models. Methods: After expressing FLAG‐tagged L166P and C106S DJ‐1 plasmids in Escherichia coli, the expressed plasmids were collected, treated with restriction enzyme, and identified using DNA electrophoresis. After purification, the L166P DJ‐1 and C106S DJ‐1 plasmids were separately transfected into SH‐SY5Y cells using liposomes. Transfected SH‐SY5Y cells were detected by western blotting and immunocytochemistry. Cell viability was determined using MTT assay. Results: Both western blotting and immunocytochemistry showed that L166P and C106S DJ‐1 were highly expressed in the transfected SH‐SY5Y cells. MTT assays showed that transfection with L166P or C106S DJ‐1 reduced the viability of SH‐SY5Y cells exposed to H2 O2, as compared to untransfected SH‐SY5Y cells. In addition, Cistanche extracts and key bioactive compounds, including acteoside, echinacoside, caffeic acid, and Cistanche total glycosides, significantly inhibited the decreases of cell viability caused by H2 O2 in L166P and C106S DJ‐1‐transfected SH‐SY5Y cells. Conclusions: These findings suggest that we successfully established sensitive and stable H2 O2 induced L166P DJ‐1‐ and C106S DJ‐1‐transfected SH‐SY5Y cell models of PD and Cistanche extracts may thus be useful for treating PD. Abstract : In this study, we established hydrogen peroxide (H2 O2 ) induced Leucine166Proline (L166P) and C106S DJ‐1‐transfected neuroblastoma (SH‐SY5Y) cellular models of Parkinson's disease (PD) and investigated the effects of Cistanche extracts, including acteoside, echinacoside, caffeic acid, and Cistanche total glycosides on these two models. We successfully established sensitive and stable H2 O2 induced L166P DJ‐1‐ and C106S DJ‐1‐transfected SH‐SY5Y cell models of PD and Cistanche extracts may thus be useful for treating PD.